MENGETAHUI PENGARUH KOEFISIEN VISKOSITAS AKUADES TERHADAP VARIASI DIAMETER TABUNG MENGGUNAKAN ADOBE AUDITION 1.5 - Salim, M Barkah (UNIVERSITAS MUHAMMADIYAH METRO, 2014)
An experiment had been carried out to determine the viscosity coefficient of aquadest (destilled water) by using Stokes falling ball method. The detection of the balltime during the experiment is done using magnetic induction censor while the reading of induction time data uses adobe audition 1.5 software. By doing this technique the measurement of magnetic ball travel time can minimize the weakness of the ball falling travel measurement which is usually done manually. In this experiment the determination of the coefficient of viscosity by varying the diameter of the tube. The purpose of this experiment was to determine the effect of tube diameter on the viscosity coefficient Â Based on the results of the experiment, the bigger the tube diameter is, the smaller the viscosity coefficient will be. If the tube diameter is bigger again, the viscosity coefficient will be flatter. So, viscosity coefficient is always constant for each of the increase of tube diameter.